Synergistic effects of cisplatin and apigenin on telomerase expression and telomerase activity in TNBC cells / Associate Professor Dr Gabriele Ruth Anisah Froemming and Noorfaiza A.Aziz - Froemming, Gabriele Ruth Anisah; A.Aziz, Noorfaiza (Research Management Institute (RMI), 2015)
Triple Negative Breast Cancer (TNBC) is highly heterogeneous and metastatic breast cancer form with a low five-year survival rate diagnosed patients. As TNBC is negative for the expression of estrogen (ER), progesterone (PR) and Her2neu receptors it has limited treatment options due to a lack of molecular targets and the heterogeneity of deregulated pathways…